1997
DOI: 10.1128/jb.179.1.63-71.1997
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a region of the IncHI2 plasmid R478 which protects Escherichia coli from toxic effects specified by components of the tellurite, phage, and colicin resistance cluster

Abstract: The IncHI2 plasmid R478 specifies resistance to potassium tellurite (Te r ), to some bacteriophages (Phi), and to pore-forming colicins (PacB). The genes encoding the three phenotypes are linked, and an 8.4-kb fragment of R478 DNA encoding them cannot be subcloned unless cocloned with a second section of the plasmid. Subclone pKFW4A contains a 5.9-kb BamHI-EcoRI fragment which caused some toxicity when present in Escherichia coli cells. Bacterial cells containing freshly transformed pKFW4A, examined by light m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 41 publications
0
59
0
Order By: Relevance
“…The majority of the tellurite-resistance research to date has centred on the ter operon from the IncH plasmids (Hill et al, 1993 ;Jobling & Ritchie, 1987Taylor et al, 1994 ;Whelan, 1992 ;Whelan et al, 1995Whelan et al, , 1997 and the kilA (or kla) operon from the IncPα plasmid RK2 (Bradley, 1985 ;Taylor & Bradley, 1987 ;Thomas et al, 1980 ;Turner et al, 1994aTurner et al, , b, 1995bWalter & Taylor, 1989). Research has also focused on the teh genes from the E. coli chromosome (Taylor et al, 1994 ;Turner et al, 1995aTurner et al, , b, 1997Walter et al, 1991b).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the tellurite-resistance research to date has centred on the ter operon from the IncH plasmids (Hill et al, 1993 ;Jobling & Ritchie, 1987Taylor et al, 1994 ;Whelan, 1992 ;Whelan et al, 1995Whelan et al, , 1997 and the kilA (or kla) operon from the IncPα plasmid RK2 (Bradley, 1985 ;Taylor & Bradley, 1987 ;Thomas et al, 1980 ;Turner et al, 1994aTurner et al, , b, 1995bWalter & Taylor, 1989). Research has also focused on the teh genes from the E. coli chromosome (Taylor et al, 1994 ;Turner et al, 1995aTurner et al, , b, 1997Walter et al, 1991b).…”
Section: Introductionmentioning
confidence: 99%
“…The polypeptide encoded by the H. pylori pss gene was expressed in a derivative of maxicell strain CSR603 (40), namely, CSRDE3, carrying the P lac -controlled T7 RNA polymerase gene on the chromosome (52). Initially, the wild-type pss gene was amplified from pBSHpC10 and cloned into pBluescript KSĎŞ.…”
Section: Resultsmentioning
confidence: 99%
“…Nucleotide sequence was determined with thermocycling Sequenase purchased from Amersham Life Science, Inc. (Cleveland, Ohio), following the procedure specified in the supplier's manual. The pss gene was expressed in modified maxicell strain E. coli CSRDE3 cells (52) and analyzed by sodium dodecyl sulfate-polyacrylamide (15%) gel electrophoresis as described previously (10). Plasmid mutants were introduced into H. pylori UA802 by a natural transformation procedure (50).…”
Section: Methodsmentioning
confidence: 99%
“…These genes protect many Enterobacteria from the toxic effects of potassium tellurite but parts of the ter operon, especially terA and terZ, have also been shown to be toxic to host cells when overexpressed or expressed without the protective terW gene product. The unusual filamentous morphology of E. coli cells harbouring the ter genes cloned into the pUC13 plasmid (plasmid pKFW4A) was described by Whelan et al (1997), who divided the operon into protective (upstream of terZ gene) and toxic (downstream of, and including, the terZ gene) regions. They found that chromosomal DNA replication was not inhibited and proposed that the unusual filamentous morphology was caused by the inhibition of cell division.…”
Section: Discussionmentioning
confidence: 99%
“…(Jobling & Ritchie 1987); it has also been found on the plasmid pHH1508a (IncHII) from Klebsiella aerogenes (Walter & Taylor 1989), the large conjugative plasmid pR478 (IncHI2) from Serratia marcescens (Whelan et al 1997) and the chromosomes of Proteus mirabilis (Toptchieva et al 2003) and Escherichia coli O157:H7 (Perna et al 2001). Several enteric pathogens share a similar locus of ter genes, which provides the high level resistance that is currently used for the isolation and identification of many pathogens, including the emergent enterohemorrhagic E. coli O157:H7 strain (Zadik et al 1993).…”
Section: Introductionmentioning
confidence: 99%